Mecamylamine-precipitated nicotine withdrawal syndrome and its prevention with baclofen: An autoradiographic study of α4β2 nicotinic acetylcholine receptors in mice - Varani, Andrés Pablo (2013)
A previous study from our laboratory showed that baclofen (BAC, GABAB receptor agonist) was able to prevent the behavioral expression of nicotine (NIC) withdrawal syndrome. To further investigate the mechanisms underlying this effect, we conducted this study, with the aims of analyzing α4β2 nicotinic receptor density during NIC withdrawal and, in case we found any changes, of determining whether they could be prevented by pretreatment with BAC. Swiss Webster albino mice received NIC (2.5 mg/kg, s.c.) 4 times daily, for 7 days. On the 8th day, NIC-treated mice received the nicotinic antagonist mecamylamine (MEC; 2 mg/kg, i.p.) 1 h after the last dose of NIC. A second group of NIC-treated mice received BAC (2 mg/kg, i.p.) prior to MEC administration. Thirty minutes after MEC, mice were sacrificed and brain autoradiography with [3H]epibatidine was carried out at five different anatomical levels. Autoradiographic mapping showed a significant increase of α4β2 nicotinic receptor labeling during NIC withdrawal in the nucleus accumbens shell (AcbSh), medial habenular nucleus (HbM), thalamic nuclei, dorsal lateral geniculate (DLG) nucleus, fasciculus retroflexus (fr), ventral tegmental area, interpeduncular nucleus and superior colliculus. BAC pretreatment prevented the increased α4β2 nicotinic receptor binding sites in the AcbSh, MHb, thalamic nuclei, DLG nucleus and fr. The present results suggest a relationship between BAC´s preventive effect of the expression of NIC withdrawal signs, and its ability to restore the changes in α4β2 nicotinic receptor labeling, evidenced in specific brain areas in NIC withdrawn animals.